Catalogue of European & American paintings : 1500-1900 : New York World's Fair 1940 (Nueva York: Art Aid Corporation, 1940)
New York World's Fair, 1940
Keywords: PINTORES; DATOS BIOGRAFICOS; Exposiciones; FERIAS DE ARTE; PINTURA